STUDENTS' PERCEPTIONS ON ONLINE LEARNING FOR INTERMEDIATE LISTENING COURSES THROUGH E-LEARNING DURING THE COVID-19 PANDEMIC - Bradhiansyah Tri Suryanto; Hirtsul Arifin; Khalid Al-Madani (Nurul Jadid University, 2021)
This study aims to determine the perceptions of English Education students at Nurul Jadid University, Probolinggo towards online learning for intermediate listening courses via E-learning during the Covid-19 pandemic. After one semester's learning process, the qualitative descriptive method was carried out by distributing questionnaires using Google Form to 48 2nd semester students of English Education at Nurul Jadid University, Probolinggo. The results of this study stated that the performance aspects of using UNUJA's E-learning for Intermediate Listening courses are as expected, the effort aspect of using E-Learning UNUJA for Intermediate Listening courses are as expected, social factors of using E-Learning UNUJA for Intermediate Listening courses are still less than expected, aspects of conditions that facilitate the use of E-Learning UNUJA for Intermediate Listening courses are considered very good, student interest in using E-Learning UNUJA for Intermediate Listening courses is very high, and behavioural aspects of using E-Learning UNUJA for Intermediate Listening is good.